Physical and Mechanical Properties of Chitosan Bioplastics with Ramie Fiber Concentration Variations - Umi Jamilah; Sujito; N. Hidayatillah; E. Hidayah (BRIN Publishing (Penerbit BRIN), 2026)
Bioplastics are biodegradable materials derived from natural polymers such as starch, cellulose, lignin, or chitosan and are considered sustainable alternatives to conventional plastics. In this study, chitosan-based bioplastics were prepared using chitosan extracted from fish scales and reinforced with alkali-treated ramie fibers. Chitosan was dissolved in 1% acetic acid at 50 °C for 4 h, followed by the addition of 5% citric acid and ramie fibers at various contents (15%, 20%, 25%, and 30% relative to chitosan mass), and stirred for an additional hour. The resulting bioplastics were characterized for tensile strength, elastic modulus, water absorption, and surface morphology using SEM. The results indicate that ramie fiber content significantly influences the mechanical and physical properties of the bioplastics. Increasing the fiber content generally enhances tensile strength and reduces water absorption; however, excessive fiber loading can lead to performance deterioration. The optimum formulation was achieved at 25% ramie fiber, exhibiting a tensile strength of 39.60 MPa, an elastic modulus of 43.35 MPa, and a reduction in water absorption of approximately 43% compared to fiber-free bioplastics, along with a more homogeneous surface structure. These findings demonstrate that ramie fiber reinforcement effectively improves the performance of chitosan-based bioplastics.